The Use of Rifapentine for Preventive Chemotherapy in Children from Risk Groups of Developing Tuberculosis - O. D. Baronova; V. A. Aksenova; E. F. Luginova; E. N. Dolzhenko (Туберкулез и болезни лёгких)
The objective: to compare efficacy of preventive treatment of children with latent tuberculosis infection using various regimens of anti-tuberculosis drugs and assess the risk of adverse events to these drugs.Subjects and Methods. 117 children of 2-17 years old with latent tuberculosis infection [a positive result of the test with tuberculous recombinant allergen (TRA)] were enrolled in the prospective study. They received preventive treatment with the regimen containing isoniazid and rifapentine. The comparison group included 84 children who received isoniazid and rifampicin.Results. In terms of safety and efficacy of chemotherapy regimens in the study, the best results were obtained when using the regimen containing isoniazid and rifapentine: the therapy was well tolerated, hepatotoxic reactions were registered in 1.7% of children. After a full course of preventive treatment in 24 months of follow-up, there was a statistically significant decrease in the proportion of hyperergic results of the skit test with TRA from 44 (41.9%) to 0 (0%) χ2 McNemar 43.00; p < 0.01; and conversion of the TRA test result from positive to negative was observed in 18.1% of children.